Single nucleotide polymorphisms (SNPs) of the MC1R gene in black and brown alpacas - Pinares, Rubén (2021)
In alpacas color fleece phenotypes have different terminologies that induces confusion within the brown color and its shades, it requires a better description and quantification. Consequently, the aims of the study were to quantify the color of fiber and identify the informational SNPs in the MC1R gene (melanocortin 1 receptor) in brown and black alpacas. A vicuña phenotype (n=14) and four alpaca phenotypes (n=79), light brown, dark brown, brown-black and black were evaluated by colorimetry. The vicuña fleece showed greater lightness (47.74) and color intensity (24.33) compared to brown alpacas. The CIE L*a*b* values (lightness and intensity) suggest low values in eumelanic alpacas and high in pheomelanic alpacas. In vicuña and alpaca, the coding sequence of the MC1R gene has a single exon of 954 bp, in vicuñas the deletion (c.224_227del) was not observed. However, this deletion was observed in three alpaca phenotypes (light brown, dark brown and black), as well as the five non-synonymous SNPs described in other populations, c.82A>G, c.259G>A, c.376G>A, c.587T>C, c.901C>T (p.T28A, p.M87V, p.G126S, p.F196S, and p.R301C). Eight haplotypes defined by the five SNPs were identified in both species. The associations between color phenotypes and SNPs were not observed (p>0.05), probably due to the influence of other genes such as ASIP on color expression. Our results as well as previous studies showed highly conserved regions in the coding sequence of the MC1R gene.